Hubungan antara Intensitas Penggunaan Gawai dengan Perubahan Pola Tidur Pelajar Sekolah Menengah Atas - Sangu, Yolenta C.; Wahyuni, Octavia D. (e-CliniC, 2025)
Abstract: Good sleep quality results in physiological and psychological balance upon awakening. Using gadgets for a long duration will affect sleep pattern. This study aimed to obtain the relationship between gadget use and changes in sleep pattern among high school students. This was an analytical and observational study with a cross-sectional design. Samples were students of SMA Regina Pacis Jakarta (senior high school), obtained by using consecutive non-random sampling technique. Sleep patterns were categorized using the PSQI questionnaire. Data were analyzed with Fisher's Exact Test. The results showed that most respondents had high-intensity device use behavior (88.4%), and most respondents had poor sleep pattern (97.6%). The statistical test obtained a p-value of 0.000 and PR 2.68 for the relationship between the intensity of gadget use and sleep patterns. In conclusion, there is a significant relationship between the intensity of gadget use and changes in sleep pattern among students of SMA Regina Pacis Jakarta. Students using gadgets with high intensity will have poor sleep patterns 2.68 times higher than those using gadgets with moderate intensity. Keywords: intensity of gadget use; sleep patterns; senior high school students Abstrak: Kualitas tidur yang baik menghasilkan keseimbangan fisiologis dan psiklogis pada saat terbangun. Penggunaan gawai dengan durasi lama akan memengaruhi pola tidur seseorang. Penelitian ini bertujuan untuk mengetahui dampak penggunaan gawai terhadap perubahan pola tidur siswa/i Sekolah Menengah Atas. Jenis penelitian ini ialah analitik observasional dengan desain potong lintang. Sampel penelitian ialah siswa/i SMA Regina Pacis Jakarta, diperoleh dengan teknik consecutive non-random sampling. Pola tidur dikategorikan menggunakan kuesioner Pittsburgh Sleep Quality Index (PSQI). Uji analisis statistik menggunakan Fisher’s Exact Test. Hasil penelitian mendapatkan sebanyak 95 siswa/i sebagai responden. Sebagian besar responden memiliki perilaku penggunaan gawai dengan intensitas tinggi (88,4%), dan sebagian besar responden memiliki pola tidur yang buruk (97,6%). Hasil uji statistik mendapatkan nilai p=0,000 dan PR 2,68 untuk hubungan antara intensitas penggunaan gawai dengan pola tidur. Simpulan penelitian ini ialah terdapat hubungan bermakna antara intensitas penggunaan gawai dengan pola tidur pada siswa/i SMA Regina Pacis Jakarta. Pengguna gawai dengan intensitas tinggi akan memiliki pola tidur buruk sebanyak 2,68 kali lebih tinggi dibandingkan yang menggunakan gawai dengan intensitas sedang. Kata kunci: intensitas penggunaan gawai; pola tidur; pelajar SMA